2022
DOI: 10.1002/fsn3.2724
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanocomposite alginate‐based film incorporated with cumin essential oil and TiO2 nanoparticles on chemical, microbial, and sensory properties of fresh meat/beef

Abstract: The environmental problems of synthetic plastics in food packaging have led researchers to synthesize biodegradable films. In this study, nanocomposite alginate‐based films containing TiO2 nanoparticles (1%) and cumin essential oil (CEO, 2%) were fabricated and the potential of these films to protect beef from chemical [pH, total volatile base nitrogen (TVBN), peroxide value, and thiobarbituric acid reactive substances (TBA)] and microbial [total viable count, Enterobacteriaceae, lactic acid bacteria, Listeria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 74 publications
(116 reference statements)
0
0
0
Order By: Relevance
“…To measure the pH values of the meat samples using a pH meter (Jenway pH meter 350; Dunmow, Essex, UK), first, the device was calibrated by buffer solutions with different pH, and then 10 g of meat was poured into a container with 90 mL of distilled water and stirred with a glass rod. Finally, the pH value of the sample was read and recorded by the pH meter at room temperature [26].…”
Section: Determination Of Ph and Tvb-nmentioning
confidence: 99%
“…To measure the pH values of the meat samples using a pH meter (Jenway pH meter 350; Dunmow, Essex, UK), first, the device was calibrated by buffer solutions with different pH, and then 10 g of meat was poured into a container with 90 mL of distilled water and stirred with a glass rod. Finally, the pH value of the sample was read and recorded by the pH meter at room temperature [26].…”
Section: Determination Of Ph and Tvb-nmentioning
confidence: 99%
“…A study Lee et al [80] that used thyme EO in skin gelatin-based active films showed an increase in antibacterial activity on Listeria monocytogenes and Escherichia coli O157:H7. Similarly, Sayadi et al [81] used cumin EO in alginate/TiO 2 active films, which reduced the total mesophilic bacteria and lipid oxidation, extending the shelf life of beef. Cardoso et al [82] and Souza et al [43], respectively, used Origanum vulgare oil (EOE) and cinnamon EO in PBAT-based active films and reported that these oils successfully provided active functions in biodegradable films and improved the elastic modulus, elongation, and thermal stability properties of the resulting films.…”
Section: Application Of Biodegradable Films Packaging For Foodmentioning
confidence: 99%
“…In cellulose films added with curcumin addictive substances [73], curcumin provides strong antioxidant activity and can reduce fat oxidation in fresh pork. Similarly, Sayadi et al [81] added cumin EO as an antimicrobial agent in alginate/TiO 2 films and reported that the film can reduce the population of total mesophilic bacteria and extend the shelf life of fresh beef while maintaining its color and sensory quality.…”
Section: Overview Of Social Environmental and Economic Aspectsmentioning
confidence: 99%
“…Alginates/S NPs composite film can be used as packaging material for frozen foods with high moisture content which are susceptible to contamination of Listeria monocytogenes (e.g., meat products) [93]. Various other active food packaging material have been developed by incorporating metal and metal oxide (TiO2, ZnO) and essential oil or plant extract, such as cumin essential oil, Alovera, oregano essential oil, cottonseed protein hydrolysates, which have the proven potential application in packaging of fish, meat and fatty foods (Table 1) [94][95][96][97].…”
Section: Alginatesmentioning
confidence: 99%